The superparamagnetic iron oxide tracer: a valid alternative in sentinel node biopsy for breast cancer treatment. (14th September 2015) - Ghilli, M.; Carretta, E.; Di Filippo, F.; Battaglia, C.; Fustaino, L.; Galanou, I.; Di Filippo, S.; Rucci, P.; Fantini, M.P.; Roncella, M.
Abstract : The European Union has determined that from 2016 breast cancer patients should be treated in Specialist Breast Units that achieve the minimum standards for the mandatory quality indicators as defined by Eusoma. The existing standard for axillary lymph node staging in breast cancer is sentinel node biopsy (SNB), performed using Technetium‐sulphur colloid ( 99m Tc) alone or with blue dye. The major limits of radioisotope consist in the problems linked to radioactivity, in the shortage of tracer and nuclear medicine units. Among existing alternative tracers, SentiMag ®, which uses superparamagnetic iron oxide particles, can represent a valid option for SNB. We conducted a paired, prospective, multicentre study to evaluate the non‐inferiority of SentiMag ® vs. 99m Tc. The primary end point was the detection rate (DR) per patient. The study sample consists of 193 women affected by breast carcinoma with negative axillary assessment. The concordance rate per patients between 99m Tc and SentiMag ® was 97.9%. The DR per patient was 99.0% for 99m Tc and 97.9% for SentiMag ® . SentiMag ® appears to be non‐inferior to the radiotracer and safe. While 99m Tc remains the standard, SentiMag ® DR appears adequate after a minimum learning curve. In health care settings where nuclear medicine units are not available, SentiMag/Sienna+ ® allows effective treatment of breast cancer patients.